CHARACTERIZATION OF COMPOSITE MATERIALS OBTAINED BY ELECTROLYTIC METHOD - Minodora Maria PASĂRE (Fiabilitate şi Durabilitate)
Composite materials can be defined in different ways, because, through the variation of working parameters, there is the possibility of making a large number of combinations between the constituents from which these composites are formed, a fact that leads to the ability to modulate their properties and the realization in this way of a wide palette of materials that can be used in almost all spheres of activity. The deposits of composite materials obtained by electrolytic method give a special appearance to the surface and ensure protection against corrosion and wear and are a solution to increase the performance and reliability of the parts. The properties of Ni-P/SiC electrodepositions, in which SiC particles are embedded, vary depending on the working conditions. A parameter that greatly influences the hardness of these composites is the amount of phosphorous acid in the electrolyte. The hardness tests show that depending on this parameter (and implicitly also the phosphorus content that is incorporated into the layer) the hardness varies according to three composition domains. By applying variable loads, the hardnesses decrease as the loads increase.